Feasibility and Safety of Pleuroscopic Cryobiopsy of the Pleura: A Prospective Study - Chia-Hung Chen; Wen-Chien Cheng; Biing-Ru Wu; Chih-Yu Chen; Wei-Chun Chen; Wei-Chih Liao; Chih-Yen Tu (Canadian Respiratory Journal)
Background. The aim of this study was thus to evaluate the feasibility and safety of taking biopsy specimens by cryoprobe from the parietal pleura during semirigid pleuroscope. Methods. In a single-center, observational, prospective study, patients with exudative pleural effusion (EPE) were evaluated with a semirigid pleuroscope between January 2015 and July 2017. Each patient underwent pleural biopsy using flexible forceps and flexible cryoprobe through pleuroscope following diagnostic thoracentesis and closed pleural biopsy (CPB). Results. A total of 92 patients (median age 64 years) were included in the study, most of whom were men (65.2%). Cytological cell block (CCB) and CPB made definitive diagnoses in 32/92 (34.8%) and 25/92 (27.5%), respectively; flexible forceps biopsy (FFB) and cryoprobe biopsy (CB) established definitive diagnoses in 84/92 (91.3%) and 91/92 (98.9%), respectively. The sample obtained by CB (9.4 ± 4.9 mm) was significantly larger than the other two methods: FFB (4.2 ± 2.3 mm) or CPB (1.9 ± 1.0 mm) (P<0.0001). The immunohistochemical (IHC) staining was more easily performed with CB (98.9%) compared to either FFB (87.0%) or CPB (13.0%). There were no significant complications or procedure-related deaths. Conclusions. Based on these results, CB during semirigid pleuroscope has a high diagnostic yield, differentiating EPE of unknown etiology with satisfactory effectiveness and safety.